The Influence of the Pouring Temperature on the Structure and Properties of Copper Metal Alloys; Key Engineering Materials; Vol. 685 : High Technology: Research and Applications 2015 (HTRA 2015) - Korchmit A. V. Anton Viktorovich (Mechanical Engineering Technology, 2016)
Title screen